An East-Asian-type cagA Helicobacter pylori Infected Patient with Clinical Manifestation of Gastric Ulcer - Yudith Annisa Ayu Rezkitha; Muhammad Miftahussurur; Iswan A Nusi; Ummi Maimunah; Pangestu Adi; Yoshio Yamaoka (Acta Medica Indonesiana)
We reported a male, 72 yo, Chinese ethnic with chief complaint black mushy defecation. Physical examination revealed pale on conjunctival palpebra which confirmed as anemia on complete blood count. Gastroduodenoscopy revealed a 3 mm ulcer at the antrum (Forrest stage III). H. pylori infection was positive based on five different test methods (urinary antibody tests, rapid urease test, culture, histology ad immunohistochemistry). Used polymerase chain reaction-based sequencing, we found the patient infected by CagA producing, East-Asian-type cagA and vacA s1m1-strain. Further analysis using 7 housekeeping genes confirmed that the strain categorized in to hspEAsia group. The patient was given continuous intravenous infusions of proton pump inhibitor and standard triple therapy regimens eradication of H. pylori.